A Survey on Visual Perception for RoboCup MSL Soccer Robots. (8th February 2013) - Li, Xun; Lu, Huimin; Xiong, Dan; Zhang, Hui; Zheng, Zhiqiang
Visual perception is the most important method for providing information about the competition environment for RoboCup Middle Size League (MSL) soccer robots. The paper reviews the advancement of visual perception in RoboCup MSL soccer robots from several points of view including the design and calibration of the vision system, the visual object recognition, the estimation of the object's motion, robot visual self-localization and multi-robot cooperative sensing. The research progress we have achieved is also introduced in this review. The developing trends and the future research focuses on this problem are also discussed.